Modern Pollen–Plant Diversity Relationships Inform Palaeoecological Reconstructions of Functional and Phylogenetic Diversity in Calcareous Fens - Blaus, Ansis; Reitalu, Triin; Gerhold, Pille; Hiiesalu, Inga; Massante, Jhonny Capichoni; Veski, Siim (Frontiers in Ecology and Evolution, 2020)
Predicting the trajectory of ongoing diversity loss requires knowledge of historical development of community assemblages. Long-term data from palaeoecological investigations combined with key biodiversity measures in ecology such as taxonomic richness, functional diversity (FD), phylogenetic diversity (PD) and environmental factors expressed as Ellenberg indicator values (EIVs) could provide that knowledge. We explored the modern pollen–plant (moss polster pollen vs surrounding vegetation) diversity relationships for herbaceous and woody taxa in calcareous fens from two different regions in Estonia, NE Europe. Associations of taxonomic richness, vegetation composition, FD (including functional alpha diversity and trait composition), PD and EIVs in modern pollen vs plant data were studied with correlation analysis, Procrustes analysis and linear regression models. To test their potential use in palaeoreconstructions, diversity measures were applied on pollen data from Kanna spring fen reflecting fen vegetation development over the last nine millennia and diversity changes through time were studied using generalized additive models. Results showed significant pollen–plant richness correlations for herbaceous taxa at vegetation estimate scales up to 6 m radius and Procrustes analysis showed significant compositional associations at all plant estimate scales (up to 100 m). Woody taxa had no significant pollen–plant richness correlations but composition relationships were significant at plant estimate scales of 6–100 m. Traits that were best reflected by pollen data (both in terms of trait composition and functional alpha diversity) among woody and herbaceous taxa were seed number, clonality, SLA and LDMC. PD of herbaceous species was reflected by pollen data. Among the EIVs, Ellenberg L and T were significantly reflected by pollen data for both woody and herbaceous communities. Palaeoreconstruction from Kanna fen indicates that trends of woody taxa are mostly related to long-term changes in climate while diversity variables of herbaceous taxa closely follow autogenic processes within the fen. We suggest that pollen-based diversity estimates should be calculated separately for woody and herbaceous taxa as they clearly represent different spatial scales. Present study suggests that linking sedimentary pollen data with FD, PD and EIVs provides possibilities to examine long-term trends in community assembly and ecosystem processes that would be undetectable from traditional pollen diagrams.